Üks Uku Masingu varajane teooria numinoossest - Espak, Peeter (Usuteaduslik Ajakiri, 2010)
One early theory about numinous by Uku Masing The paper discuss one early theory of Uku Masing who tried to establish a connection between the different terms associable with the general notion of the numinous: the Sumerian word inim, the Hebrew term dbr YHWH and Polynesian mana. Some textual examples about the use of Sumerian inim (“word“) are discussed and it is concluded that it is used similarly to its Hebrew counterpart dbr but has no close or identical associations with the Polynesian mana. Some considerations about the Polynesian mana are also treated in the paper and it is argued that the similarities or equation of mana and inim/dbr are hard to detect. However, it is concluded that from the Sumerian culture and language several concepts or words close to „the numinous force“, such as mana, are detectable: me, he-gal and me-lem4.